Designing High‐Performance LED Phosphors by Controlling the Phase Stability via a Heterovalent Substitution Strategy. Issue 2 (21st November 2019) - Cheng, Chen; Ning, Lixin; Ke, Xiaoxing; Molokeev, Maxim S.; Wang, Zelin; Zhou, Guojun; Chuang, Yu‐Chun; Xia, Zhiguo
Abstract: Phosphor‐converted white light‐emitting diodes (LEDs) are currently playing key roles in the lighting and display industries and trigger urgent demands for the discovery of "good" phosphors with high quantum efficiency, improved thermal stability, and controllable excitation/emission properties. Herein, a general and efficient heterovalent substitution strategy is demonstrated in K2 HfSi3 O9 :Eu 2+ achieved by Ln 3+ (Ln = Gd, Tb, Dy, Tm, Yb, and Lu) doping to optimize luminescence properties, and as an example, the Lu 3+ substitution leads to improvement of emission intensity and thermal stability, as well as tunable emission color from blue to cyan. The structural stability and Eu 2+ occupation via Lu 3+ doping have been revealed by the structural elaboration and density functional theory calculations, respectively. It is shown that heterovalent substitution allows predictive control of site preference of luminescent centers and therefore provides a new method to optimize the solid‐state phosphors for LEDs. Abstract : Heterovalent substitution in hosts accelates the discovery of high performance light‐emitting diode (LED) phosphors with high quantum efficiency, low thermal quenching and tunable emission. Combining experimental evidence and density functional theory calculations provides an understanding of the structural stability and Eu 2+ occupation via Lu 3+ doping in K2 HfSi3 O9 :Eu 2+ phosphor. The authors' results demonstrate a facile predictive control of photoluminescence for LED phosphors.